The night listener - Stettner, Patrick; Collette, Toni.; Williams, Robin, 1952 July 21-; Morton, Joe, 1947-; Cannavale, Bobby; Culkin, Rory.; Rinzler, Lisa.; Nashel, Pete.; Maupin, Armistead; Miramax Home Entertainment (Firm); Buena Vista Home Entertainment (Firm) (Burbank, CA : Miramax Home Entertainment : Distributed by Buena Vista Home Entertainment, 2007)
In the midst of his crumbling relationship, a radio show host begins speaking to his biggest fan, a young boy, via the telephone. But when questions of the boy's identity comes up, the host's life is thrown into chaos.
English track: Dolby digital 5.1 surround.
Title from container.
Based on the novel by Armistead Maupin.
Originally released as a motion picture in 2006.
Bonus features: deleted scene; 'The Night listener revealed' : and in-depth look at the movie's plot twists.
Director of photography, Lisa Rinzler ; editor, Andy Keir ; music, Peter Nashel ; costume designer, Marina Draghici ; production designer, Michael Shaw.
Keywords: Radio talk shows -- United States -- Drama; Fans (Persons) -- Drama; Interpersonal relations -- United States -- Drama; Feature films; Thrillers (Motion pictures, television, etc.); Films for the hearing impaired; Detective and mystery films